Effects of Resistance Footrest on Spine Posture in Visual Display Terminal Workers - Won-gyu Yoo (Korean Research Society of Physical Therapy, 2021)
Background: Flat-back posture refers to a posture in which the pelvis is tilted backward, the lumbar spine is bent, the upper thoracic spine is increasingly bent, and the lower thoracic spine is straight. Given that most of the day is spent sitting, we need to develop exercise programs and devices that are suitable for people who spend less time exercising than sitting. Objects: This study investigated the effects of resistance footrest exercise on spine posture angles in visual display terminal (VDT) workers with flat back. Methods: We measured the upper lumbar angle (ULA) and lower lumbar angle (LLA) using a flexible ruler for the ULA and LLA. Then, after 1 week of resistance footrest exercise designed to strengthen the lumbar spine musculature, we measured these angles again. We measured each angle three times and then compared measurements from before and after exercise. Results: There were no significant differences in the ULA following the strengthening exercise, but significant differences were observed in LLA. Conclusion: The resistance footrest exercise strengthened the muscles affecting the pelvic and lumbar lordotic angles, and increases in the LLA were changed. This suggests that the role of the lower lumbar spine in the lumbar lordotic curve is greater than that of the upper lumbar spine. In addition, considering the contemporary tendency to lead fairly sedentary lives, these results indicate that exercising while seated can be effective.